2021
DOI: 10.1093/rheumatology/keab343
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of biologic DMARDs in a real-world population of patients with rheumatoid arthritis in remission: outcome and risk factors

Abstract: Objectives Data from randomized controlled trials have shown the feasibility of discontinuation of bDMARD therapy in patients with RA that have reached remission. Criteria for selecting patients that are likely to remain in remission are still incompletely defined. We aimed to identify predictors of successful discontinuation of bDMARD therapy in the Swiss Clinical Quality Management (SCQM) registry, a real-world cohort of RA patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…For example, Schlager et al [ 11 ] found that a greater percentage of women did not experience a relapse after discontinuation, and Tweehuysen et al [ 27 ] found no evidence of an association between sex and possible discontinuation of bDMARDs. Our data are in line with those of most of the studies that revealed differences and agree with studies that showed differences by sex for achieving or maintaining remission or low disease activity without DMARDs in patients with RA and AS [ 7 , 13 , 23 , 29 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Schlager et al [ 11 ] found that a greater percentage of women did not experience a relapse after discontinuation, and Tweehuysen et al [ 27 ] found no evidence of an association between sex and possible discontinuation of bDMARDs. Our data are in line with those of most of the studies that revealed differences and agree with studies that showed differences by sex for achieving or maintaining remission or low disease activity without DMARDs in patients with RA and AS [ 7 , 13 , 23 , 29 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that concomitant csDMARD therapy was negatively associated with discontinuation on achieving remission, although this association was not confirmed in the analysis at 6 months. Previous studies, such as that by Tweehuysen et al [ 27 ] in patients with RA or the CRESPA study in patients with peripheral AS [ 36 ], found no positive or negative association for this factor, although in studies that did in fact show differences in maintenance of bDMARD-free remission, taking csDMARDs was positively associated with this possibility [ 31 , 32 ]. In clinical practice, discontinuation of bDMARDs may be easier for patients whose disease progresses well and who do not therefore require a csDMARD, but for whom this could prove useful for ensuring bDMARD-free treatment in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Although female sex was previously suggested to be negatively associated with bDMARD-free remission [ 9 , 10 , 21 ], a study of a randomized controlled trial assessing sustained infliximab-free remission reported that sex was not a relevant variable after adjusting for other confounding factors [ 23 ]. Moreover, smoking [ 24 ] and seronegativity [ 7 , 8 ] were previously reported to be predictors of sustained bDMARD-free remission.…”
Section: Discussionmentioning
confidence: 99%
“…A recently performed study in the same database (SCQM) by Arnold et al [ 9 ] assessed the time to loss of remission defined by either DAS28 ≥ 2.6 or b/tsDMARD restart. Arnold et al reported that 76% of patients lost remission within a median time of 9 months, whereas we observed that 59% of patients achieved sustained b/tsDMARD-free remission of ≥12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Such success has already been achieved in rheumatoid arthritis, largely with the widespread use of effective targeted therapy using monoclonal antibodies. 12,15 Effective monoclonal antibody therapies are now increasingly used in asthma, 16,17 raising the hope of asthma remission as a realistic therapeutic goal. In this review, we critically evaluate the current concept of asthma remission, what it constitutes, the prevalence and predictors of remission, the pathophysiology of remission, the possibility of achieving remission in the current clinical environment and future research directions (Figure 1).…”
Section: Introductionmentioning
confidence: 99%